Urinary metabonomic study of Panax ginseng in deficiency of vital energy rat using ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. (26th May 2016) - Lin, He; Pi, Zifeng; Men, Lihui; Chen, Weijia; Liu, Zhiqiang; Liu, Zhongying
Abstract: Ethnopharmacological relevance: Deficiency of vital energy (DE) is called Qi-deficiency, a traditional Chinese medicine syndrome. It is an indicator of a disease emerging though fuzzy, dynamic, complex, nonspecific and subjective. Ginseng is regarded as the king of herbs. It is famous for the function of replenishing qi in traditional Chinese medicine. It has treatment potential for DE caused by various reasons. This study aimed to investigate the mechanism of ginseng treating symptom DE with the method of metabolomics. Materials and methods: Thirty-five rats were randomly divided into three groups: normal control group, DE model group and ginseng treatment group. The DE model rats were administered daily with ginseng decoctiondecoctiondecoction intragastrically and others with water for 15 days. Urine was analyzed with ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). Principal component analysis (PCA) and orthogonal projection to latent structures squares-discriminant analysis (OPLS-DA) were built to distinguish the three groups in this study and find potential biomarkers. Results: The three groups are clearly separated and find out their metabolic distinction in PCA score plots. It showed that the metabolic profile of ginseng treatment group was changed to normal control group after administration of ginseng. Fifteen potential biomarkers are identified by OPLS-DA including Xanthurenic acid, kynurenic acid, Pantothenic acid, which are chiefly involved in tryptophan metabolism, taurine and hypotaurine metabolism, citric acid cycle, bile acid biosynthesis, alpha linolenic acid and linoleic acid metabolism. These biomarkers and the networks of their corresponding pathways will help to explain the mechanism of DE and ginseng treatment. Conclusions: The results of blood biochemical indicators routine and urinary metabonomic reveal that ginseng have good abilities to regulate the energy metabolism, immune function and antioxidant activities. And UPLC-Q-TOF-MS-based metabolomics can provide useful information for the understanding of metabolic changes in DE rats after administration of ginseng in urine. The biomarkers and their corresponding pathways will provide further information of the mechanisms of ginseng in treating DE. This work also proves that the method of metabonomics is effective in traditional Chinese medicinal research. Graphical abstract: